Sobre(vivências): modos de vida, trabalho e institucionalização dos pescadores artesanais de São Francisco-MG (1960-2014) - Pereira, Roberto Mendes Ramos (2015)
Survival/experiences: lifestyles, work and institutionalization of artisanal fishermen of São Francisco - Minas Gerais (1960-2014) it is a thesis about the ways of survival of artisanal fishermen who deal with pressures of all forms in the last decades, be in the issue of taking care of their families, be fighting for access to fishing and to the São Francisco River. It is a research in the field of Social History, whose theoretical and methodological references are based mainly on work of E. P. Thompson, Raymond Williams, Antonio Gramsci and Alessandro Portelli. There are several sources worked, such as: journals, legislation, official projects, newsletters, bulletins, statistical overviews occurrence and, above all, a set of 26 interviews. The aim is to highlight the struggle for hegemony in the spaces of the life and work of artisanal fishers, focusing on the struggles and achievements of rights, but also showing that these subjects have been placed in a condition of such vulnerability in recent years which, in pursuit of survival/experience, have become much more a legal figure, holder of rights and duties, than a reality in the riverbed, living and working as a professional fisher.